Evolusi Pendidikan Islam dari Konsep Klasik Menuju Paradigma Modern - Anam, Ahsanul (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
This study examines the evolution of Islamic education from the classical concept to the modern paradigm through the perspective of the thoughts of Ibn Khaldun and Muhammad Abduh. Ibn Khaldun, with his theory of the cycle of civilization, provides an analytical framework for the dynamics of change in Islamic education. Meanwhile, Muhammad Abduh, as a reformer, offers ideas for reforming Islamic education that are relevant to the challenges of the modern era. This study analyzes how these two figures view the importance of integrating religious knowledge and general knowledge, and its impact on the development of contemporary Islamic education. The purpose of this study is to explore the transformation of Islamic education from the classical to the modern era, focusing on the contributions of the thoughts of Ibn Khaldun and Muhammad Abduh. Ibn Khaldun emphasized the importance of adapting education to social and political changes, while Muhammad Abduh called for the renewal of the curriculum and teaching methods. This article compares and analyzes the views of these two figures on the goals, methods, and challenges of Islamic education, as well as their relevance to current efforts to modernize Islamic education. This research method uses a comparative analysis of the thoughts of Ibn Khaldun and Muhammad Abduh.